2007
DOI: 10.1007/s11906-007-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Agonist autoantibodies against the angiotensin AT1 receptor in renal and hypertensive disorders

Abstract: Previous studies demonstrated the significance of an agonistic angiotensin II receptor AT1 autoantibody (AT1-AA) in preeclampsia. Because of its ability to release calcium in vascular smooth muscle cells, stimulate reactive oxygen species, and initiate proinflammatory processes, this antibody was thought to be important in the etiology and pathogenesis of preeclampsia. Recent investigations, however, have broadened and refined the pathobiological relevance of this antibody and refuted its role as the primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…31, 32 It is not clear whether AT1RaAbs are specific disease-causing agents, or if their levels reflect age-related global dysregulation of autoantibody production. Autoantibodies in general are capable of stimulating receptors and causing disease, such as Graves’ disease 33 and dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…31, 32 It is not clear whether AT1RaAbs are specific disease-causing agents, or if their levels reflect age-related global dysregulation of autoantibody production. Autoantibodies in general are capable of stimulating receptors and causing disease, such as Graves’ disease 33 and dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the agonistic function of an antibody when it cross-links its target, the mechanism of action may depend on the signaling capacity and biological function of the ligand as with HLA I molecules. For example, angiotensin II receptor AT1 autoantibodies are well-established agonists, which promote hypertension and may contribute to renal allograft rejection [146148]. Antibodies from autoimmune sera upregulate adhesion molecules and cytokines on endothelial cells [149151], but when the target is unknown the precise mechanism remains elusive.…”
Section: Non-hla Antibodiesmentioning
confidence: 99%
“…However, abnormal autoimmune response is a pathogenic factor contributing to and promoting the occurrence of cardiovascular diseases [5]. Since Wallukat el al [6] detected AT1-AA in the serum of preeclamptic patients in 1999, AT1-AA have been detected in the serum of patients with various cardiovascular diseases and those who underwent kidney transplantation [7]. Xia et al reported that AT1-AA were detectable six weeks earlier in the serum of patients with reduced uterine perfusion as compared with the preeclamptic patients.…”
Section: Introductionmentioning
confidence: 99%